A Comparative Analysis of Tintern Abbey and Frost at Midnight from the Perspective of Ecocriticism - Ahmad, Jawad; Jian, Luo (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2024)
This comparative analysis exploits the framework of ecocriticism to explore the themes of nature and the environment in William Wordsworth's